Bond convenience curves and funding costs - Juuso Nissinen; Markus Sihvonen (Bank of Finland, 2022)
A convenience yield represents a difference between yield on a safe bond and yield on a synthetic safe bond, constructed by combining a risky bond with a CDS contract. We explain the shapes of eurozone sovereign convenience curves using a model in which arbitrageurs face higher funding costs on bonds with credit risk and bond demand shocks induce funding risk. We provide novel causal evidence for our mechanism using variation in funding costs generated through exogenous haircut category changes. Changes in convenience yields represent a key transmission channel of unconventional monetary policy to bond yields.
urn:nbn:fi:bof-202209281394
Keywords: G12; G15; 330; Sovereign bond convenience yields; money markets; asset pricing with frictions; monetary policy